Introduction to numerical electrostatics using MATLAB - Dworsky, Lawrence N., 1943- (Hoboken, New Jersey : John Wiley & Sons Inc., 2014)
"The first of its kind uniquely devoted to the field of computational electrostatics, this book dives headfirst into the actual problems that engineers are expected to solve using method of moment (MoM), finite difference, and finite element techniques. Readers are guided step by step through specific problems and challenges, covering all aspects of electrostatics with an emphasis on numerical procedures. Focusing on practical examples, mathematical equations, and common issues with algorithms, this is an ideal text for students in engineering, physics, and electrostatics--and working engineers and physicists"--
"Introduction to Numerical Electrostatics contains problem sets, an accompanying web site with simulations, and a complete list of computer codes"--
8.5 Voltages and Fields8.6 Stored Energy and Capacitance; Problems; 9 Refining the Finite Difference Method; 9.1 Refined Grids; 9.2 Arbitrary Conductor Shapes; 9.3 Mixed Dielectric Regions and a New Derivation of the FiniteDifference Equation; 9.4 Example: Structure with a Dielectric Interface; 9.5 Axisymmetric Cylindrical Coordinates; 9.6 Symmetry Boundary Condition; 9.7 Duality, and Upper and Lower Bounds to Solutions forTransmission Lines; 9.8 Extrapolation; 9.9 Three-Dimensional Grids; Problems; 10 Multielectrode Systems; 10.1 Multielectrode Structures; 10.2 Utilizing Superposition.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: Electromagnetism -- Data processing; Electrostatics -- Data processing; SCIENCE -- Electromagnetism; Electronic books